Keabsahan Akun Media Sosial Sebagai Harta Bersama Perkawinan Bilamana Terjadi Perceraian - Cindy Kusuma, Teresa; Karama Cupu Manik, Amethysa; Shinta Dewi Pramayanti, Putu (Recital Review, 2024)
The purpose of this journal is to gain an understanding of the validity of social media accounts as part of joint assets in marriage and to identify division procedures in the event of a divorce. The aim of writing this article is to answer legal questions using normative legal research methods that combine a legislative approach with legal concepts to analyze applicable theories, concepts, legal principles and regulations. Findings from the study indicate that social media accounts can be considered marital assets if they are considered virtual property, which has an impact on the division of marital assets. Property arrangements in marriage law include two categories: inherited property and joint property. Social media accounts that are included in joint assets can trigger disputes when dividing assets when a divorce occurs. There are several solutions to resolve disputes related to social media accounts that are jointly operated as joint property, such as selling them and dividing the proceeds or making an agreement to share profits from social media account income after a divorce occurs.